InMAF: Indexing Music Databases via Multiple Acoustic Features - SHEN, Jialie (Institutional Knowledge at Singapore Management University, 2006)
Music information processing has become very important due to the ever-growing amount of music data from emerging applications. In this demonstration, we present a novel approach for generating small but comprehensive music descriptors to facilitate efficient content music management (accessing and retrieval, in particular). Unlike previous approaches that rely on low-level spectral features adapted from speech analysis technology, our approach integrates human music perception to enhance the accuracy of the retrieval and classification process via PCA and neural networks. The superiority of our method is demonstrated by comparing it with state-of-the-art approaches in the areas of music classification query effectiveness, and robustness against various audio distortion/alternatives.